Optimization of Extraction of Phlorotannins from the Arctic Fucus vesiculosus Using Natural Deep Eutectic Solvents and Their HPLC Profiling with Tandem High-Resolution Mass Spectrometry - Ekaterina D. Obluchinskaya; Olga N. Pozharitskaya; Vadim A. Shevyrin; Elena G. Kovaleva; Elena V. Flisyuk; Alexander N. Shikov (Marine Drugs, 2023)
Phlorotannins are secondary metabolites produced mainly by brown seaweeds (Phaeophyceae) and belong to the class of polyphenolic compounds with diverse bioactivities. The key factors in the extraction of polyphenols are the selection of a suitable solvent, method of extraction and selection of optimal conditions. Ultrasonic-assisted extraction (UAE) is one of the advanced energy-saving methods suitable for the extraction of labile compounds. Methanol, acetone, ethanol and ethyl acetate are the most commonly used solvents for polyphenol extraction. As alternatives to toxic organic solvents, a new class of green solvents, natural deep eutectic solvents (NADES), has been proposed for the efficient extraction of a wide range of natural compounds including polyphenols. Several NADES were screened previously for the extraction of phlorotannins; however, the extraction conditions were not optimized and chemical profiling of NADES extract was not performed. The purpose of this work was to study the effect of selected extraction parameters on the phlorotannin content in NADES extract from Fucus vesiculosus, optimization of extraction conditions and chemical profiling of phlorotannins in the NADES extract. A fast and green NADES-UAE procedure was developed for the extraction of phlorotannins. Optimization was performed through an experimental design and showed that NADES (lactic acid:choline chloride; 3:1) provides a high yield (137.3 mg phloroglucinol equivalents per g dry weight of algae) of phlorotannins under the following extraction conditions: extraction time 23 min, 30.0% water concentration and 1:12 sample to solvent ratio. The antioxidant activity of the optimized NADES extract was equal to that of EtOH extract. In total, 32 phlorotannins have been identified (one trimer, two tetramers, six pentamers, four hexamers, six heptamers, six octamers and seven nonamers) in NADES extracts from arctic F. vesiculosus using the HPLC-HRMS and MS/MS technique. It was noted that all the above-mentioned phlorotannins were ...